NILAI-NILAI PEMBENTUK KARAKTER DALAM FILSAFAT SOSROKARTONO - Mulyono, Mulyono (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
Nowdays, the people of Indonesia face some crisis as a result of modernization and globalization.. One most alarming crisis is the weak character that caused demoralization of the social life of the Indonesian nation. This nation will be able to take advantage of modernization and globalization for the progress and superiority, when she has strong character and resilient. Character formation can be done through education from school, community, and family. Character education materials can be sourced from religion, five principles of Pancasila, and local wisdom. One local wisdom has come from the philosophy of Sosrokartono, laden content of values forming the character of Indonesian nation. There are seven values forming the character, as part of the eighteen values formulated by the Ministry of National Education, which can be taken from the philosophy of Sosrokartono. These seven values to forming character that can be taught and disseminated to the public include religious values, honesty, friendly and communicative, love of peace, social care, responsibility, and humanity.